Identification of sports injuries in senior volleyball athlete age 17-24 years - Deddy, Deddy Whinata; Novia Dewi , Mutiara (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2024)
The problem of this study is the frequent occurrence of injury in volleyball in athletes aged 17-24 years old at PBV Vita Solo, the frequent occurrence is possibly caused by the lack of knowledge of the coach on the type and cause of the injury. The type of this research is qualitative research. To identify the type and cause of injury in volleyball athlete is by using closed questionnaire and interview. The result of this research is the injuries occurred in volleyball athletes at PBV Vita Solo are: minor injury 85.33% consists of bruises and cramps, moderate injury 12.36% consists of detached joint injury as an injury that ever occurred and strain and sprain injuries as uncommon injury, severe injury 2.32% consists of fracture, strain, and sprain where these three injuries are uncommon. The occurrence of injuries to female athletes has a percentage of injuries of minor injury 85.56%, moderate injury 12.83%, meanwhile male athletes have a higher percentage of severe injury 4.17%. In internal and external factors there are similarities as the most common cause of injury where internal factor is 66.48% and external factor is 33.52%.